(untitled) (World Economics and Finance Bulletin, 2026)
This article details the factors representing the economic potential of the industrial sector and the econometric approaches used to evaluate them. A classification of econometric modeling of socio-economic processes and a mechanism for analyzing industrial production have been developed. In addition, priority directions for improving economic indicators and its further development in assessing the potential of the industrial sector are proposed